Monitoramento da qualidade da água de represas e avaliação de riscos aos sistemas de irrigação - Favero, Daiane (2018)
The construction of dams is the attempt to increase the availability of water resources to meet human needs. In the north of Espírito Santo, this technique is widely used in the storage of water for use in irrigation, and has increased due to long periods of drought. However the quantity and quality of the waters of these dams may vary and affect the applicability for use in irrigation. Thus, the objective of this work was to study physico-chemical and hydrochemical variables of water quality in newly constructed dams, and others already existent, in the north of Espírito Santo, to identify possible risks to irrigation systems. The monitoring was carried out in 4 dams in Nova Venécia-ES (P1 to P4) and another 4 dams in the municipality of São Mateus-ES (P5 to P8). The hydrochemical variables analyzed in this study were pH, temperature, dissolved oxygen (DO), electrical conductivity (EC), total solids (ST), turbidity, total iron (FeT), Fe2+ and Fe3+, orthophosphate (PO4 3- ), sulfate SO4 3- ), sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), hardness, alkalinity (HCO3-) and chloride (Cl- ). In addition, data of water level of the dams, rain regime and solar irradiation were obtained. Data were evaluated through descriptive statistics (maximum, minimum, mean and standard deviation), according to the risk class of damage to the irrigation system and with the Piper diagram, through the QualiGraf program. The high concentrations of iron and total solids recorded in the dam waters of Nova Venécia and São Mateus, tending to a higher concentration in new dams, make it impossible to use these waters directly for irrigation. In these cases, the treatment of water is indispensable and allows its use with reduction of possible damages to the irrigation system, so irrigators should be aware of the use of filters, aerators and decanters to prevent the passage of these elements, preventing the deposition along the irrigation system. irrigation system. For the other parameters studied the majority of the samples presented acceptable results. The Nova Venécia and São Mateus dams presented their waters mainly in C1S1 classes, of high quality for irrigation. Few samples were classified in class C2S2 in this case these waters should be used in soils of good permeability and with a certain degree of leaching and to opt for more tolerant plants. As for the hydrochemical classification of the waters of both municipalities, they were mostly chlorinated sodium, with small seasonal compositional variations.